2009
DOI: 10.1021/es901891t
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Controls on the Complexation between Mercury and Dissolved Organic Matter in a Contaminated Environment

Abstract: The interaction of mercury (Hg) with dissolved natural organic matter (NOM) under equilibrium conditions is the focus of many studies but the kinetic controls on Hg-NOM complexation in aquatic systems have often been overlooked. We examined the rates of Hg-NOM complexation both in a contaminated Upper East Fork Poplar Creek (UEFPC) in Oak Ridge, Tennessee, and in controlled laboratory experiments using reducible Hg (Hg(R)) measurements and C(18) solid phase extraction techniques. Of the filterable Hg at the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
151
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(158 citation statements)
references
References 30 publications
(55 reference statements)
7
151
0
Order By: Relevance
“…The complexation chemistry between mercury and organic substances, including natural organic matter (NOM), dissolved organic matter (DOM), and dissolved organic carbon (DOC), have been studied by different researchers (Barkay et al, 1997;Benoit et al, 1999;Benoit et al, 2001;Kelly et al, 2003;Miller et al, 2007;Miller et al, 2009;Zhong and Wang, 2009;Dong et al, 2010). The kinetics of NOM complexation with mercury was studied by Miller et al (2009).…”
Section: Chemistry Of Mercurymentioning
confidence: 99%
See 3 more Smart Citations
“…The complexation chemistry between mercury and organic substances, including natural organic matter (NOM), dissolved organic matter (DOM), and dissolved organic carbon (DOC), have been studied by different researchers (Barkay et al, 1997;Benoit et al, 1999;Benoit et al, 2001;Kelly et al, 2003;Miller et al, 2007;Miller et al, 2009;Zhong and Wang, 2009;Dong et al, 2010). The kinetics of NOM complexation with mercury was studied by Miller et al (2009).…”
Section: Chemistry Of Mercurymentioning
confidence: 99%
“…The kinetics of NOM complexation with mercury was studied by Miller et al (2009). In their research, Miller et al (2009) concluded that the kinetics of mercury complexation with NOM needs to be evaluated the dominant complexes of Hg in aquatic systems receiving input of inorganic Hg.…”
Section: Chemistry Of Mercurymentioning
confidence: 99%
See 2 more Smart Citations
“…Generally in stratified systems, concentrations of total mercury and methyl mercury are higher near the sediments [12]. The kinetics of mercury with dissolved organic matter in aquatic ecosystems requires additional evaluation as the dominant complexes are difficult to determine [13]. Table 1.…”
mentioning
confidence: 99%